Body-temperature programmable shape memory UV resin - Woo, Jetson (Nanyang Technological University, 2023)
The purpose of this project was to reconstruct 3D-printing resin to gain shape memory properties. Investigation into the material properties was done on the specimens through testing the mechanical response to cyclic loads and shape memory performance of the SMH specimens.